Descripción de la morfología microscópica de comunidades de nostoc sp, provenientes de la parroquia de Pintag provincia de Pichincha. - Ortega Tapia, Geovanny Daniel (2016)
This research describes the microscopic morphology of Nostoc sp., from Pintag (Pichincha), in relation to weather variables from May to September 2015. The features evaluated from the samples were: diameter of cells (µm), heterocyst diameter (µm), mucilage area (µm²), filament length (µm) and heterocyst number in relation to one hundred vegetative cells. Fifteen samples were analyzed using as reference the temperature, precipitation, relative humidity and solar radiation. Each sample was hydrated and settled on plates with methylene blue to be observed with a microscopy. In the data analysis, according to Pearson correlations, the heterocyst number, filament length and mucilage area do not present any correlation with the weather variables studied. Vegetative cells diameter, displayed correlation with the solar radiation (r = 0.95 / p= 0.01) but does not present any kind of correlation with the other weather variables (p>0.05). The heterocyst diameter indicated that solar radiation is correlated (r = 0.93 / p=0.019), the same for the relative humidity (r = -0,89 / p=0.04), but the temperature and precipitation (p>0.05) do not present correlation. Multiple lineal regression shows correlation between heterocyst number vs. temperature, solar radiation and precipitation, showing that morphological variables depend on the surrounding weather conditions.